2010
DOI: 10.1094/pdis-03-10-0221
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure and Resistance to Mefenoxam of Phytophthora capsici in New York State

Abstract: In 2006, 2007, and 2008, we sampled 257 isolates of Phytophthora capsici from vegetables at 22 sites in four regions of New York, to determine variation in mefenoxam resistance and population genetic structure. Isolates were assayed for mefenoxam resistance and genotyped for mating type and five microsatellite loci. We found mefenoxam-resistant isolates at a high frequency in the Capital District and Long Island, but none were found in western New York or central New York. Both A1 and A2 mating types were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
79
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 41 publications
2
79
0
Order By: Relevance
“…As a result, the genus has been the focus of many population biology studies (Bhat and Browne 2007;Bhat et al 2006;Bienapfl and Balci 2014;Cooke et al 2003Cooke et al , 2005Dobrowolski et al 2003;Donahoo and Lamour 2008;Duan et al 2008;Dunn et al 2010;Eggers et al 2012;Gevens et al 2008;Hantula et al 2000;Hulvey et al 2010;Ivors et al 2004;Lamour and Hausbeck 2001;Linde et al 1997Linde et al , 1999. These studies have shown that population structures can vary considerably between different regions and species.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the genus has been the focus of many population biology studies (Bhat and Browne 2007;Bhat et al 2006;Bienapfl and Balci 2014;Cooke et al 2003Cooke et al , 2005Dobrowolski et al 2003;Donahoo and Lamour 2008;Duan et al 2008;Dunn et al 2010;Eggers et al 2012;Gevens et al 2008;Hantula et al 2000;Hulvey et al 2010;Ivors et al 2004;Lamour and Hausbeck 2001;Linde et al 1997Linde et al , 1999. These studies have shown that population structures can vary considerably between different regions and species.…”
mentioning
confidence: 99%
“…These studies have shown that population structures can vary considerably between different regions and species. For example, populations of Phytophthora cactorum in the United States, England, and Finland were shown to have lower genetic diversity (Bhat et al 2006;Hantula et al 2000) than populations of P. citricola, P. capsici, P. nicotianae, and P. infestans from agricultural or nursery systems (Bhat and Browne 2007;Dunn et al 2010;Lamour and Hausbeck 2001;Shattock 1988).…”
mentioning
confidence: 99%
“…Repeated use of metalaxyl and mefenoxam has resulted in the selection of resistant isolates of F capsici (9,21,28,(31)(32)(33). Resistance to metalaxylbased products necessitates additional fungicides and novel methods" of fungicide application to improve control of F capsici.…”
mentioning
confidence: 99%
“…It is interesting that until the year 2012 no natural recombinants of P. ramorum have been observed (Grünwald et al 2012). In contrast, among P. capsici populations from the USA and South Africa the occurrence of sexual reproduction and high levels of genetic diversity have been described (Dunn et al 2010;Gobena et al 2012;Meitz et al 2010). Although in populations of P. capsici from Peru and in most provinces of China asexual clonal lineages dominate (Hu et al 2013;Hurtado-Gonzales et al 2008).…”
Section: Introductionmentioning
confidence: 99%